Analysis Of Palm Oil Carbon Stock Generating Plant Phase (TM - Sari Anggraini; Yudha Wiratama Arifin (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Stored carbon is present in plant stands by measuring plant biomass. The amount of carbon stock depends on the diversity and density of existing plants, soil types and management methods. The purpose of this study was to determine whether or not there is an effect of differences in pyrite land on the size of carbon sequestration in oil palm plantations in the Production Plant (TM) phase (<20 years). This research was conducted in May - September 2020. The research sample was taken at the oil palm plantation of PT. Mopoli Raya, part of payarambe, North Sumatra. The test and calculation of carbon stocks were carried out at the Laboratory of PPKS Medan North Sumatra. The design of this study used a descriptive design, namely the non-destructive sampling method for measuring the biomass of living trees, dead trees and dead wood and the sampling method by harvesting (destructive sampling) for measuring the biomass of understorey plants and litter. Observations on sample plots according to plant age class with pyrite planting conditions. From the results of this research, oil palm (Elaeis guineensis Jacq) can be concluded that the carbon stock of pyrite land is greater.